Heat Transfer Characters of Non-azeotropic Mixtures in Evaporator - 朱强 (Zhileng xuebao)
In order to know heat transfer characters of non-azeotropic mixtures in the evaporator of air conditioner or heat pump systems, and to understand special function of temperature gliding in engineering, the theoretical analysis was carried out using heat transfer and thermodynamics theories. The results show that the non-azeotropic mixtures had less energy loss than single fluids. In addition, it is found that the maximum evaporation medium flow rate occurred in heat transfer process. Finally, the maximum evaporation medium flow rates and energy loss were predicted for some popular non-azeotropic mixtures including R407c, R405a, and R414b.